Dekonstruksi Prinsip Mengajar Rabi Yudaisme Berdasarkan Matius 23:3 sebagai Upaya Menemukan Hakikat Pendidikan Kristen di Indonesia - Erman Saragih; Andar Gunawan Pasaribu; Johari Manik (Harati: Jurnal Pendidikan Kristen, 2023)
The relationship between Christian continuity and Judaism is also a fascinating study in terms of the practice of Christian education. The implementation of Christian Education often goes too far in referring to material from the teachings of Rabbi Judaism in the process of its implementation without stating the affirmation of the nature of Christian Education itself on that reference. The purpose of this manuscript is as an anti-thesis of the Jewish rabbinic teaching pattern "... they teach it but don't practice it," which was strongly criticized by Jesus and as a reflection of the implementation of Christian Education in Indonesia. The method used is descriptive qualitative with a literature review. The conclusion is, first, it is necessary to affirm the nature of Christian Education among the educational principles of the rabbis in the context of its time because the teachings of Jesus are very much in contrast to the teachings of Judaism. Second, the challenges of implementing Christian education in Indonesia are diverse and multi-layered, so it is full of teaching dichotomies. Third, the pattern of teaching Jesus as a fundamental principle for implementing Christian Education is not to get trapped and make mistakes made by Jewish rabbis. Jesus emphasized the practice of justice, love, and faithfulness